2021
DOI: 10.15177/seefor.21-15
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Deposition in Different Mediterranean Forest Types along the Eastern Adriatic Coast

Abstract: Mediterranean forests along the eastern Adriatic coast have an important ecological role. However, few studies have been conducted on nitrogen deposition so far. To improve this knowledge, the main aims of our study were: (i) to estimate nitrogen inputs and determine differences among the four Mediterranean forests, (ii) to determine the seasonal behaviour of N deposition compounds, and (iii) to discuss the results in relation to forest type and precipitation. Measurements were carried out over a two-year peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In our study, this same process could be observed in the undefoliated pubescent oak and Aleppo pine trees as a defense mechanism. It is possible that the trees may have also been under stress due to environmental conditions in the Mediterranean region, such as high concentrations of ozone and a large amount of nitrogenous and acidic compounds [7,8,34]. Although the results showed a mostly optimal concentration of nutrients (Table 1), various factors affect the resistance of the examined species, and the concentration of nutrients could not be considered as a potential cause of stress in the tested species.…”
Section: Foliar Nutrition Status Of Four Selected Mediterranean Speciesmentioning
confidence: 90%
See 2 more Smart Citations
“…In our study, this same process could be observed in the undefoliated pubescent oak and Aleppo pine trees as a defense mechanism. It is possible that the trees may have also been under stress due to environmental conditions in the Mediterranean region, such as high concentrations of ozone and a large amount of nitrogenous and acidic compounds [7,8,34]. Although the results showed a mostly optimal concentration of nutrients (Table 1), various factors affect the resistance of the examined species, and the concentration of nutrients could not be considered as a potential cause of stress in the tested species.…”
Section: Foliar Nutrition Status Of Four Selected Mediterranean Speciesmentioning
confidence: 90%
“…In our previous investigations, we examined the effects of air pollution on the condition of the forest ecosystem by analyzing tree vitality and obtained interesting results [7,8,34]. For example, higher levels of N, acid compounds, and ozone concentrations were measured in dominant forest species along the Adriatic coast [7,8,34].…”
Section: Relationship Between Defoliation Oxidative Stress Indicators...mentioning
confidence: 99%
See 1 more Smart Citation